2016
DOI: 10.3389/fcimb.2016.00187
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Innate Immune Response to a Staphylococcus aureus Small Colony Variant Compared to Its Wild-Type Parent Strain

Abstract: Background: Staphylococcus aureus (S. aureus) small colony variants (SCVs) can survive within the host intracellular milieu and are associated with chronic relapsing infections. However, it is unknown whether host invasion rates and immune responses differ between SCVs and their wild-type counterparts. This study used a stable S. aureus SCV (WCH-SK2SCV) developed from a clinical isolate (WCH-SK2WT) in inflammation-relevant conditions. Intracellular infection rates as well as host immune responses to WCH-SK2WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 44 publications
2
20
0
1
Order By: Relevance
“…Here we showed there to be no difference in ability to invade cells between pairs of an isogenic SCV or closely related SCV and an NCP S. epidermidis isolate (see Fig. S2E and F in the supplemental material), as previously shown for S. aureus (65). In addition, we showed a positive correlation between SCV formation and time of intracellular persistence in human fibroblasts with multiple staphylococcal strains and extended these findings to infection in osteoblasts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here we showed there to be no difference in ability to invade cells between pairs of an isogenic SCV or closely related SCV and an NCP S. epidermidis isolate (see Fig. S2E and F in the supplemental material), as previously shown for S. aureus (65). In addition, we showed a positive correlation between SCV formation and time of intracellular persistence in human fibroblasts with multiple staphylococcal strains and extended these findings to infection in osteoblasts.…”
Section: Discussionsupporting
confidence: 88%
“…( Fig. S2C), suggesting that SCVs do not have an increased ability to invade cells in comparison to NCP isolates, as previously shown for one S. aureus NCP and SCV pair (65).…”
Section: Resultssupporting
confidence: 80%
“…Pathogens also alter their phenotype to adjust themselves within the epithelium to cause chronic infections. A small colony variant of Staphylococcus aureus often persists intracellularly including in the epithelium due to its ability to exert minimal inflammatory response compared to wild type strains (30). These examples demonstrate a wide array of pathogen mechanisms to outsmart epithelial phagocytosis, which contributes to the disease pathogenesis.…”
Section: How Pathogens Circumvent Phagocytic Abilitymentioning
confidence: 99%
“…For example, the poor drug loading capacity and instability of the liposomes remain important issues. 41 Low loading capacity of polymeric nanoparticles for the polar antimicrobial agents is always faced due to the mutual repulsion between the hydrophilic active molecules and the hydrophobic polymers. The lack of reasonable large-scale production is still another bottleneck for polymeric nanoparticles.…”
Section: Current Challengesmentioning
confidence: 99%
“…39 It was reported that the intracellular infection of WCH-SK2 wild-type promoted the expression of much more factors (TLR2, tissue remodeling factors, and proinflammatory cytokines) than WCH-SK2 SCV (only upregulated expression of TLR2). 40 In addition, the metabolism level and growth of SCVs will be slower than the normal phenotype due to the obstacle of tricarboxylic acid metabolism and energy production, [41][42][43][44] because of dependence to hemin, menadione and thymidine. 1,45…”
mentioning
confidence: 99%